If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (x + -2y + -7) * dx + (2x + -4y + 1) * dy = 0 Reorder the terms: (-7 + x + -2y) * dx + (2x + -4y + 1) * dy = 0 Reorder the terms for easier multiplication: dx(-7 + x + -2y) + (2x + -4y + 1) * dy = 0 (-7 * dx + x * dx + -2y * dx) + (2x + -4y + 1) * dy = 0 Reorder the terms: (-7dx + -2dxy + dx2) + (2x + -4y + 1) * dy = 0 (-7dx + -2dxy + dx2) + (2x + -4y + 1) * dy = 0 Reorder the terms: -7dx + -2dxy + dx2 + (1 + 2x + -4y) * dy = 0 Reorder the terms for easier multiplication: -7dx + -2dxy + dx2 + dy(1 + 2x + -4y) = 0 -7dx + -2dxy + dx2 + (1 * dy + 2x * dy + -4y * dy) = 0 Reorder the terms: -7dx + -2dxy + dx2 + (2dxy + 1dy + -4dy2) = 0 -7dx + -2dxy + dx2 + (2dxy + 1dy + -4dy2) = 0 Reorder the terms: -7dx + -2dxy + 2dxy + dx2 + 1dy + -4dy2 = 0 Combine like terms: -2dxy + 2dxy = 0 -7dx + 0 + dx2 + 1dy + -4dy2 = 0 -7dx + dx2 + 1dy + -4dy2 = 0 Solving -7dx + dx2 + 1dy + -4dy2 = 0 Solving for variable 'd'. Move all terms containing d to the left, all other terms to the right. Factor out the Greatest Common Factor (GCF), 'd'. d(-7x + x2 + y + -4y2) = 0Subproblem 1
Set the factor 'd' equal to zero and attempt to solve: Simplifying d = 0 Solving d = 0 Move all terms containing d to the left, all other terms to the right. Simplifying d = 0Subproblem 2
Set the factor '(-7x + x2 + y + -4y2)' equal to zero and attempt to solve: Simplifying -7x + x2 + y + -4y2 = 0 Solving -7x + x2 + y + -4y2 = 0 Move all terms containing d to the left, all other terms to the right. Add '7x' to each side of the equation. -7x + x2 + y + 7x + -4y2 = 0 + 7x Reorder the terms: -7x + 7x + x2 + y + -4y2 = 0 + 7x Combine like terms: -7x + 7x = 0 0 + x2 + y + -4y2 = 0 + 7x x2 + y + -4y2 = 0 + 7x Remove the zero: x2 + y + -4y2 = 7x Add '-1x2' to each side of the equation. x2 + y + -1x2 + -4y2 = 7x + -1x2 Reorder the terms: x2 + -1x2 + y + -4y2 = 7x + -1x2 Combine like terms: x2 + -1x2 = 0 0 + y + -4y2 = 7x + -1x2 y + -4y2 = 7x + -1x2 Add '-1y' to each side of the equation. y + -1y + -4y2 = 7x + -1x2 + -1y Combine like terms: y + -1y = 0 0 + -4y2 = 7x + -1x2 + -1y -4y2 = 7x + -1x2 + -1y Add '4y2' to each side of the equation. -4y2 + 4y2 = 7x + -1x2 + -1y + 4y2 Combine like terms: -4y2 + 4y2 = 0 0 = 7x + -1x2 + -1y + 4y2 Simplifying 0 = 7x + -1x2 + -1y + 4y2 The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined.Solution
d = {0}
| -3m^2+2m-1=0 | | 2m-3m^2-1=0 | | 3/4×75 | | 3-4(5t-17)=-69 | | (5w-6)(3-w)=0 | | 8.7-4.7(x+2.3)=7-3(x+4) | | 5(2x-6)=30 | | 4ab-2b-2a= | | (132x)7-14x=0 | | 7x-2(x-5)=5(x+1)+8 | | 5x-9=5x+30-39 | | x-7=11/2 | | 7x-7x=25 | | x=20xy | | (x+7)*(x+3)= | | y=31292e(-0.2x) | | y=31292e-(9) | | (x+7)-(x+3)= | | 180=(180-(2x+60))+(3x+10)+x | | y=31292e-(0.2x) | | 180=(-180+(2x+60))+(3x+10)+x | | (x+7)+(x+3)= | | 180=(-180+2x+60)+(3x+10)+x | | 180=2x+3x+-180+60+10 | | 5(x-2)+4(x+2)=14-4x | | 4+-9x=9x+-2 | | 6=3sqrt | | 8x=-4x+-3x | | -16(t^2+4t+5)=0 | | d=1/16*8^2 | | d=1/16*7^2 | | d=1/16*9^2 |